Three anatomical levels: possibilities to decrease invasiveness of reconstructive surgery for congenital penile curvature - Perdzyński, Wojciech (Cent European J Urol, 2017)
INTRODUCTION: The aim of the study was to report methods – based on penile anatomy – leading to the minimization in the invasiveness of reconstructive surgery for congenital penile curvature (CPC). MATERIAL AND METHODS: From 2006 to 2016 authors operated on 186 adult men with CPC. To avoid degloving, the authors used the longitudinal skin and tunica dartos incision. For decreasing invasiveness to the dorsal neurovascular bundle (NVB), the authors separated it only locally in the shape of a triangle or a trapezium, elevating it only over the place of the tunical reconstruction. To decrease the invasiveness for the tunica albuginea (TA) and cavernous vessels, a new operative technique based on the stratified structure of the TA was developed in which the corpora cavernosa were not opened. During reconstruction, only the elliptical fragment of the external layer of the tunica was excised (internal layer was left intact) and both layers of the tunica were sutured over the invaginated internal layer. RESULTS: Follow-up ranged from 6 months to 10 years. In all the patients, the penis was straightened during operation. Follow-up examinations were done 6 months and 1 year postoperatively. Disorders of superficial sensation on the glans, erectile dysfunction or chronic postoperative edema were not detected in any of the 186 patients. The penis remained straight in 180 patients (96.7%). In 4 patients (2.2%) in whom the primary curvature was 80–90 degrees and the postoperative curvature was about 30 degrees, reoperation was done. In two patients (1.1%) with the remaining postoperative curvature up to 20 degrees and good functional result (patient's opinion), there was no need for further treatment. CONCLUSIONS: Longitudinal skin and tunica dartos incision on the convex surface of the penis allows for the ability to avoid penile degloving and to preserve the foreskin. Elevation of the dorsal NVB from the TA was done on a very limited surface in the shape of triangle or trapezium, in order to decrease the possibility of dorsal nerves/vessels damage. Excision of elliptical fragments of the external layer of the TA with subsequent invagination of the internal layer, excluded the need for opening of the corpora cavernosa as well as for the use of a tourniquet during reconstruction. This diminished the potential risk of complications, especially intra- and postoperative bleeding.